KARATERISTIK ENKAPSULASI LIPOSOM EKSTRAK SUPEROKSIDA DISMUTASE (SOD) Bacillus altitudinis - Nurfitriyawatie Nurfitriyawatie; Ana Indrayati; Rizal Maarif R. (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Photoaging causes the dermis and collagen fibers to decrease which results in skin aging. Genus Bacillus has SOD activity as an anti-photoaging agent that can neutralize ROS (Reactive Oxygen Species) due to exposure to UV-A rays. This study aimed to examine the activity of crude extract and the encapsulation characteristics of liposomes from B. altitudinis. The study began with the isolation of the SOD enzyme, determination of the total protein content of the crude extract of the SOD enzyme and liposome encapsulation, then characterization liposome tes including particle size analysis, sorption efficiency and zeta potential. The results of the crude extract activity test were 85.09% ± 1.24%. The characteristic test was produced with a size of 112.96 ± 17.3 ; the adsorption efficiency was 81.1% and the zeta potential was 7.0 ±5.1 mV. The results showed that the SOD B. altitudinis liposomes were in the nanoparticle range.